The Impact of Information Technology Implementation in Accounting on the Effectiveness of Management Decision Making: A Qualitative Study - Putro, Harjono Padmono (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study aims to investigate the impact of information technology (IT) implementation in accounting on the effectiveness of management decision-making, focusing on the role of advanced IT tools such as ERP systems, cloud computing, and blockchain in enhancing decision quality, especially in small and medium-sized enterprises (SMEs). A qualitative research design was employed, utilizing a systematic literature review approach to gather and analyze relevant studies on IT implementation in accounting. The research examined various factors affecting decision-making processes and the benefits and challenges of integrating IT into accounting systems. The findings indicate that implementing IT significantly enhances the quality of managerial decision-making by providing real-time, accurate data. This study demonstrates how advanced accounting systems' high-quality information directly affects the effectiveness and efficiency of decision-making. Moreover, external factors such as regulatory changes and market dynamics are critical in moderating the relationship between IT and decision-making outcomes. The study highlights the need for organizations, particularly SMEs, to prioritize IT integration in their accounting practices. Practical implications include fostering a culture of innovation, providing comprehensive training, and regularly assessing IT infrastructure to improve decision-making processes and maintain a competitive edge.